JURIDICAL ANALYSIS OF THE ROLE AND RESPONSIBILITIES OF IMMIGRATION CONTROL ON THE USE OF PASSPORTS FOR INDONESIAN MIGRANT WORKERS (PMI) IN A NONPROCEDURAL BASIS FROM THE PERSPECTIVE OF LEGAL CERTAINTY (RESEARCH STUDY AT THE CLASS I IMMIGRATION OFFICE SPE - Ricky Rahmawan; Fadlan; Erniyanti (RADJA PUBLIKA, 2023)
The departure of Indonesian Migrant Workers (PMI) was under the pretext of protecting Indonesian citizens abroad. This is certainly not in line with the constitution, so there needs to be improvements to the procedures for protecting Indonesian Migrant Workers (PMI). The domino effect is that these non-procedural Indonesian Migrant Workers (PMI) will continue to try to leave